An overview of heavy‐atom derivatization of protein crystals. Issue 3 (1st March 2016) - Pike, Ashley C. W.; Garman, Elspeth F.; Krojer, Tobias; von Delft, Frank; Carpenter, Elisabeth P.
Abstract : This review summarizes the reasons why the heavy‐atom derivatization of protein crystals can be useful, how to select heavy atoms, how to produce a heavy‐atom‐modified crystal that still diffracts and how to determine whether the protein has been modified. Abstract : Heavy‐atom derivatization is one of the oldest techniques for obtaining phase information for protein crystals and, although it is no longer the first choice, it remains a useful technique for obtaining phases for unknown structures and for low‐resolution data sets. It is also valuable for confirming the chain trace in low‐resolution electron‐density maps. This overview provides a summary of the technique and is aimed at first‐time users of the method. It includes guidelines on when to use it, which heavy atoms are most likely to work, how to prepare heavy‐atom solutions, how to derivatize crystals and how to determine whether a crystal is in fact a derivative.